The Effect of Plasticizer Molecular Weights and Concentrations on Water Vapor Permeability of Hydroxy Propyl Methyl Cellulose Films - S. HONARY; P. EBRAHIMI; N. EMRANI (International Journal of Pharma and Bio Sciences, 2010)
Plasticizers are added to improve the mechanical and conditional quality of film coating. However, other properties of coating solutions such as viscosity, droplet size and water vapor permeability (WVP) of free films be affected by incorporation of plasticizers. In this study, films of various viscosity grades of hydroxypropyl methylcellulose (HPMC) without and with different molecular weights (MWs) of polyethylene glycol (PEG) as plasticizer were prepared by a casting/solvent evaporation process and their water vapor permeability coefficient (Rwvp) were calculated. The results showed that, addition of 10% w/w PEG 200 caused a decrease in Rwvp of all grades of HPMC (E5, E15 and E50) free films and Rwvp increased by increasing the concentration of PEG 200 from 10% to 30% w/w. The Rwvp of HPMC E5 and E50 free films increased by increasing the PEG MW from 200 to 1500, but using higher MWs of PEG (4000 and 6000) caused to reduction of Rwvp. The conclusion could be drown that, as regards permeability, the addition of low MW of PEG as plasticizer at low concentration (10%) could be resulted to decrease of Rwvp of HPMC free films.